Functional outcome of displaced clavicle fractures treated with locking compression plate - S., Shivananad; A. M., Radhakrishna; N., Veeresh; Thumati, Prajwal P. (International Journal of Research in Orthopaedics, 2025)
Clavicle fractures, common in young, active individuals, often occur due to trauma or repetitive stress and account for about 2.6% to 5% of all fractures. These fractures typically happen in the midshaft and are often displaced. Historically, they were treated conservatively, but this approach often led to malunion and poor shoulder function. Recent studies show that surgical interventions, particularly with locking compression plates (LCP), improve healing, shoulder function, and reduce complications like non-union and malunion. Surgical treatments, such as open reduction internal fixation (ORIF) or closed reduction internal fixation (CRIF), are especially beneficial for displaced fractures or those with additional complications. LCPs provide better stability, especially in osteoporotic patients, although potential complications include screw loosening and infection. Overall, evidence supports surgical treatment with LCPs for better functional outcomes and fewer complications compared to nonoperative methods. This study is being done to assess functional outcome of clavicle fractures managed with open reduction with LCP. A prospective interventional study was conducted to assess functional outcome of clavicle fractures managed with ORIF with LCP. Constant-Murley score was evaluated before the treatment and were repeated after 6 weeks (T1), 12 weeks (T2) and 24 weeks (T3). The study involved 30 participants with an average age of 31.23 years, consisting of 80% males and 20% females. Of these, 53% had right-sided clavicular fractures, and 47% had left-sided fractures. Most surgeries were performed within 2-3 days of admission, with 93.33% of fractures showing union within 12 weeks. The constant Murley’s score, which measures functional outcomes, improved significantly over time: from 5.28 before surgery to 91.09 after 24 weeks. The functional outcome was graded excellent in 90% of patients. Statistical analysis showed significant improvement in scores post-surgery (p<0.001). Age had a weak positive correlation with better outcomes, while time from admission to surgery and time to union had strong negative correlations with functional outcomes. These findings suggest that faster surgery and quicker union lead to better functional recovery, and age has a slight impact on outcomes.